A bio-psycho-social approach to addiction - Linnet, Jakob (Psyke & Logos, 2005)
Welcome to this special issue of Psyke & Logos, which focuses on addictions. Several journals are dedicated to the issue of addictions (e.g. Addiction, Addictive Behaviors, and Psychology of Addictive Behaviors), yet little attention has been dedicated to the concept of addictions and the addictive component in different types of addictive behavior. Since the 60s and the 70s with the introduction and wide spread use of substances such as cannabis and opiates, there has been an increase in the multitude of substances used for recreational (i.e. non-medical) purposes including the use of cocaine and amphetamine in the 80s and 90s and so-called »designer drugs« such as ecstasy in the new millennium. At the same time, we’ve seen concerns ‘addictive behaviors’, particularly among children, associated with technological developments ranging from the use of comic books in the 60s and 70s, to the use of video films in the 80s, the use of video games in the 90s and the use of the internet and mobile phones in the new millennium. A third development is the efforts of information and reduction of health risking behavior. Most noticeably, probably, is the perceptual and behavioral changes related with tobacco use, which has resulted in a reduction of the total number of smokers as well as a reduction of smoking in public places. Other areas which have received attention in later years is eating disorders (both anorexia nervosa, bulimia, and over eating (binge eating)), as well as the efforts to inform about risk behavior of alcohol consumption among youths. The Psyke & Logos conference held on January 28, 2005 has the focus of comparing different types of addictive behavior in a conglomerate of clinical manifestations. The papers produced from the conference together with the invited papers for this issue, all present different aspects of addictive behavior, and have been chosen to provide the reader with insights into the different types of behaviors as well as different disciplinary approaches to understanding and treating addictive behavior. The papers are divided into three main categories: 1.) Approaches to addiction, 2.) New types of addiction, and 3.) Treatment of addiction.